Building design for handicapped and aged persons - Haber, Gilda M.;Blank, Thomas O.,;Chen, Alexander;Eldar, Reuben;Guffens, The M.G.;Harrison, James D. ;Henning, Donald N. ;Heumann, Leonard F. ;Kose, Satoshi;Lam, Khee Poh;Macdonald, James N. ;Preiser, Wolfgang F.E,;Shtarkshall, Miriam ;Sime, Jonathan D. ;Small, James G. (New York : McGraw Hill Education, 1992)
This monograph begins to address these far-reaching changes in the way the world works. The monograph compiles information from around the world about the current state affairs in design for the handicapped and aged so that what appears to work well can be adapted and extended, while what is not effective can be avoided.
Introduction -- 2. Barrier-free design in Japan -- 3. Barrier-free design in the United States -- 4. Barrier-free design in Canada -- Building design for the disabled in the Netherlands -- 6. Housing for the elderly and the disabled in Israel -- 7. Design for the disabled and the elderly in Singapore -- 8. Growing needs of elderly persons aging in place in subsidized housing -- 9. Response to living in buildings designed for handicapped and elderly persons -- 10. Access and egress for handicapped persons in public buildings -- 11. Non evacuation in compartmented fire-resistive buildings -- 12. Locator system with voice guidance for emergency evacuations -- 13. Techno-housing and the future: prospects and cautions -- 14. An assessment -- Research needs -- Nomenclature -- References/ Bibliography -- Contributors -- Building index -- Name index -- Subject index.
Includes bibliographical references and index.
Keywords: BARRIER-FREE DESIGN